Fever indigenous peoples and climate change : a video guide = Fiebre : pueblos indigenas y cambio climatico : guia de video. (LifeMosaic, 2010)
Consists of four short films which have been designed as resource for indigenous communities, to help share information about climate change as well as the struggles and the strategies that communities employ to defend their rights and determine their own futures. In the films we hear the stories from communities in Ecuador, Nicaragua, the Philippines and Indonesia. But the films aren't just for indigenous people, it is also for local facilitators, to help strengthen the capacity of networks and organizations in their awareness-raising and advocacy work on climate change. The films can also be used to bring indigenous peoples voices to audiences such as government officials; to all those whose work relates to indigenous peoples, forests and climate change; and in schools, universities, film festivals and other public events.